2014
DOI: 10.1108/bij-04-2012-0028
|View full text |Cite
|
Sign up to set email alerts
|

Performance measures of ISO 9001 certified and non-certified manufacturing companies

Abstract: Purpose – The purpose of this paper is to compare ISO 9001 certified and non-certified manufacturing companies with regard to performance measures, both financial and non-financial. Design/methodology/approach – A research study was carried out in 140 Greek manufacturing companies by means of a questionnaire. The questionnaire was sent by e-mail and it was requested that it should be answered by a company representative. Exploratory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 88 publications
(96 reference statements)
1
60
1
6
Order By: Relevance
“…The large majority of studies in Table 1 conclude that ISO 9001 certification has a positive and significant impact on firms' financial performance (Simmons and White, 1999;Chow-Chua et al, 2003;Mokhtar et al, 2005;Naveh and Marcus, 2007;Nair and Prajogo, 2009;Pantouvakis and Dimas, 2010;Gómez et al, 2013;Psomas et al, 2013;Fatima, 2014;Psomas and Kafetzopoulos, 2014;Chatzoglou et al, 2015) and on firms' stock prices (Docking and Dowen, 1999;Beirão and Cabral, 2002;Nicolau and Sellers, 2002;Corbett et al, 2005;Sharma, 2005;McGuire and Dilts, 2008). Despite the fact that some of the longitudinal studies have found supporting evidence in favor of causality between ISO 9001 certification and financial performance (e.g., Corbett et al, 2005;Benner and Veloso, 2008), other studies note that the positive correlation between these two variables does not mean causality between them (see Heras et al, 2002b;Dick et al, 2008).…”
Section: Previous Studies On Iso 9001 and The Financial Impact Of Cermentioning
confidence: 99%
“…The large majority of studies in Table 1 conclude that ISO 9001 certification has a positive and significant impact on firms' financial performance (Simmons and White, 1999;Chow-Chua et al, 2003;Mokhtar et al, 2005;Naveh and Marcus, 2007;Nair and Prajogo, 2009;Pantouvakis and Dimas, 2010;Gómez et al, 2013;Psomas et al, 2013;Fatima, 2014;Psomas and Kafetzopoulos, 2014;Chatzoglou et al, 2015) and on firms' stock prices (Docking and Dowen, 1999;Beirão and Cabral, 2002;Nicolau and Sellers, 2002;Corbett et al, 2005;Sharma, 2005;McGuire and Dilts, 2008). Despite the fact that some of the longitudinal studies have found supporting evidence in favor of causality between ISO 9001 certification and financial performance (e.g., Corbett et al, 2005;Benner and Veloso, 2008), other studies note that the positive correlation between these two variables does not mean causality between them (see Heras et al, 2002b;Dick et al, 2008).…”
Section: Previous Studies On Iso 9001 and The Financial Impact Of Cermentioning
confidence: 99%
“…We considered relevant aspects and approaches for this study. The measures of organizational performances are divided into two categories: financial and nonfinancial performance measures [35,36,39,40]. The performance standards were shown to have high reliability (Cronbach's alpha values ranged from 0.77 to 0.89) and content and construct validity as evidenced by convergent validity (factor loadings of respective measured items >0.50) and discriminant validity (AVE > r 2 ).…”
Section: Organizational Performancesmentioning
confidence: 99%
“…The first section covered the company's profile and the second section consisted of 16 items on SP practices and the third section consisted of 13 items on benefits (financial and nonfinancial) measured on a 1-5 Likert scale (5 represented strongly agree, most important, or strong improvement, whereas 1 represented strongly disagree, least important, or strong deterioration and 3 represented neutral, modest or fair) to assess the impact of implementation of SP practices on organizational performances. The nonfinancial performances (benefits) of the organization were generally covered by three major areas namely, local and international business performance, quality and operational performance, and social and environmental performance [35,36].…”
Section: Questionnaire Sample Design and Data Collection Proceduresmentioning
confidence: 99%
“…Manufacturing industries in pursuit of cost and time reduction without decreasing product quality [17,[19][20]. Improved product quality and on-time delivery result in improved performance [21]. Antony et al, [22] implemented Six Sigma to ensure there was an improvement in the on-time delivery which was able to cost reduction.…”
Section: Measures Of Current Manufacturing Performance (Cmp)mentioning
confidence: 99%